The development of motor abilities of students aged 8-9 years in physical education lessons - Polevoy, Georgiy Georgievich (Bangladesh Journal of Medical Science, 2024)
Background The problem of insufficient development of motor abilities of primary school children can be solved in physical education lessons at school by introducing Classical exercises. Aims and objectives To develop the responsiveness of younger students in physical education classes at school. Materials and methods The study took place in an ordinary school in Russia. All students studied 2 times a week, each physical education lesson lasted 40 minutes. The children from the control group performed the usual physical education program, and the children from the experimental group performed Classical exercises during the lesson. During the pedagogical experiment, 72 lessons were conducted in each group. The study used a test to determine the responsiveness of “Touch the ball.” The student’s T-test was used to determine the reliability of the results. Results After the study, the children from the control group improved their responsiveness by 3.1% (p>0.05), which is explained by the natural development of coordination abilities at primary school age. The data in children from the experimental group became 9.3% higher (p<0.05), which proves the effectiveness of introducing Classical exercises to physical education lessons at school. Conclusion In order to effectively develop the motor abilities of schoolchildren, including responsiveness, it is necessary to additionally perform a Classical exercise at each physical education lesson at school. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 682-689